2018
DOI: 10.3390/toxins10080330
|View full text |Cite
|
Sign up to set email alerts
|

Biological Degradation of Aflatoxin B1 by Cell-Free Extracts of Bacillus velezensis DY3108 with Broad PH Stability and Excellent Thermostability

Abstract: (1) Background: Aflatoxin contamination in food and grain poses serious problems both for economic development and public health protection, thus leading to a focus on an effective approach to control it; (2) Methods: Aflatoxin B1 (AFB1) degrading bacteria were isolated using a medium containing coumarin as the sole carbon source, and the biodegradation of AFB1 by the isolate was examined by high performance liquid chromatography, and liquid chromatography mass spectrometry; (3) Results: a bacterial strain exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
45
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 40 publications
14
45
1
1
Order By: Relevance
“…Bacillus velezensis HC6 exhibited antagonistic activity against L. monocytogenes , M. flavus and B. cereus , and a broad range of fungal pathogens, including A. flavus , A. parasiticus , A. ochraceus , A. sulphureus , F. graminearum and F. oxysporum , which often cause contamination of animal feed and affect the health and productivity of animals in poultry farming (Guerre ; Neme and Mohammed ). It has been reported that B. velezensis DY3108 could inhibit the growth of A. flavus and A. parasiticus (Shu et al ), and B. velezensis LM2303, BS87 and RK1 showed antifungal activity towards F. graminearum and F. oxysporum (Nam et al ; Chen et al ). These results support our conclusion that B. velezensis HC6 is potential to be used to reduce crop contaminations caused by pathogenic fungi.…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus velezensis HC6 exhibited antagonistic activity against L. monocytogenes , M. flavus and B. cereus , and a broad range of fungal pathogens, including A. flavus , A. parasiticus , A. ochraceus , A. sulphureus , F. graminearum and F. oxysporum , which often cause contamination of animal feed and affect the health and productivity of animals in poultry farming (Guerre ; Neme and Mohammed ). It has been reported that B. velezensis DY3108 could inhibit the growth of A. flavus and A. parasiticus (Shu et al ), and B. velezensis LM2303, BS87 and RK1 showed antifungal activity towards F. graminearum and F. oxysporum (Nam et al ; Chen et al ). These results support our conclusion that B. velezensis HC6 is potential to be used to reduce crop contaminations caused by pathogenic fungi.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the efficient elimination of mycotoxins and to the desire for a safe food supply, biological control represents an attractive choice. A range of microbes, such as bacteria [ 9 , 10 , 11 ], yeast, and fungi (e.g., nontoxigenic Aspergillus ), have been used for biocontrol aflatoxigenic Aspergillus [ 12 ]. Several biological control strategies to reduce AF contamination have been developed, including the use of non-toxic A. flavus and other fungi to inhibit aflatoxin synthesis [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bacillus velezensis has been widely used as a biological control agent in agricultural elds due to its excellent ability to suppress plant diseases [24,25]. It is considered as a potential rhizobacterial organism with extraordinary biosynthetic machinery, which can trigger innate immunity in plants [26].…”
Section: Introductionmentioning
confidence: 99%